Programmed Cell Death-Ligand 1 Expression Status in Urothelial Carcinoma According to Clinical and Pathological Factors: A Multi-Institutional Retrospective Study - Kim, Hyung Suk; Jang, Won Sik; Ham, Won Sik; Jung, Seung Il; Lee, Dong Hyun; Ku, Ja Hyeon; Ha, Hong Koo; Ku, Ja Yoon; Choi, Se Young; Chang, In Ho; Choi, Taesoo; Song, Wan; et al. (Frontiers in Oncology, 2020)
Purpose: To investigate programmed cell death-ligand 1 (PD-L1) expression status and the clinical and pathological factors related to its expression in urothelial carcinoma (UC) patients. Materials and Methods: Data from 761 UC patients who underwent testing for PD-L1 expression using the VENTANA (SP-142 immunohistochemistry assay) for measuring PD-L1 expression according to the manufacturer's protocol between February 2016 and July 2019 were retrospectively reviewed. Patients were categorized into three groups based on the percentage of tumor area covered by PD-L1-expressing tumor-infiltrating immune cells (ICs) as follows: IC0 (<1%), IC1 (≥1% and <5%), and IC2/3 (≥5%). Positive PD-L1 expression was defined as IC2/3 (≥5%). The factors related to positive PD-L1 expression were unadjusted and adjusted logistic regression analyses. Results: In the entire cohort, 213 (28%) patients showed positive PD-L1 expression. Final adjusted regression analyses for positive PD-L1 expression revealed that several factors, including intravesical BCG prior to PD-L1 testing (odds ratio [OR] 0.57, 95% confidence interval [CI] 0.37–0.96), advanced tumor stage (stage III/IV) (OR 2.04, 95% CI 1.41–2.93), and high tumor grade (OR 5.31, 95% CI 2.38–11.83) were significantly associated with positive PD-L1 expression. Conclusions: This study showed that the PD-L1 expression is associated with several clinical and pathological factors for the first time in a real-world setting. Further follow-up clinical trials should consider adjusting these factors, including intravesical BCG treatment, tumor stage and grade to clarify the utility of PD-L1 as a biomarker.